Biocatalytic Pickering Emulsions Stabilized by Lipase-Immobilized Carbon Nanotubes for Biodiesel Production - Lihui Wang; Xinlong Liu; Yanjun Jiang; Liya Zhou; Li Ma; Ying He; Jing Gao (Catalysts, 2018)
Biodiesel is a promising renewable energy source that can replace fossil fuel, but its production is limited by a lack of high-efficiency catalysts for mass production and popularization. In this study, we developed a biocatalytic Pickering emulsion using multiwall carbon nanotube-immobilized Candida antarctica lipase B (CALB@PE) to produce biodiesel, with J. curcas L. seed oil and methanol as substrates. The morphology of CALB@PE was characterized in detail. A central composite design of the response surface methodology (CCD-RSM) was used to study the effects of the parameters on biodiesel yield, namely the amount of J. curcas L. seed oil (1.5 g), molar ratio of methanol to oil (1:1–7:1), CALB@PE dosage (20–140 mg), temperature (30–50 °C), and reaction time (0–24 h). The experimental responses were fitted with a quadratic polynomial equation, and the optimum reaction conditions were the methanol/oil molar ratio of 4.64:1, CALB@PE dosage of 106.87 mg, and temperature of 34.9 °C, with a reaction time of 11.06 h. A yield of 95.2%, which was basically consistent with the predicted value of 95.53%, was obtained. CALB@PE could be reused up to 10 times without a substantial loss of activity. CALB@PE exhibited better reusability than that of Novozym 435 in the process of biodiesel production.